Implementation of Chemical Engineering Vocational Teacher Internship in Industry: A Multi-case Study at PT. Petrokimia Gresik and CV. Tirta Amara Mahesa - Diana Hartanti; Yoto Yoto; Didik Nurhadi (Belantika Pendidikan, 2022)
Vocational high schools aim to produce graduates with work-ready skills (supply and demand driven). However, the fact that VHS still contributes the most to unemployment is a concern. Teacher internships are an important program to increase teacher competence through industrial experience. This research seeks to discover how the industry can implement a productive teacher internship program for Chemical Engineering Expertise. The research method is case study qualitative including interviews, observations, and documents. The results showed that the teacher internship program in terms of supporting and inhibiting factors, and impacts at PT. Petrokimia Gresik. The developed a month-long teacher apprenticeship model from the Ministry of Industry, as well as field observations (plant tours) and competency schemes for the Cooling Tower Water Treatment utility system. Assessor LSP-P3 Indonesian Fertilizer Industry BNSP competency test Tirta Amara Mahesa follows the school's teacher apprenticeship model for one week directly in the drinking water treatment process based on the needs of the pilot school teaching factory program.